Perlindungan Hukum terhadap Penerima Lisensi Paten dalam Alih Teknologi - Kadek Devi Arta Adnyani; I Nyoman Putu Budiartha; Ni Made Puspasutari Ujianti (Jurnal Interpretasi Hukum, 2020)
License is a contract between the licensor (Licencor) with the licensee (License) in which the licensor with a payment and in certain circumstances gives permission to the licensee to use an intellectual property rights (intellectual property rights). Regarding the types of licenses according Lee and Davidson, differentiate into 2 (two) types of licenses, namely Exclusive and Non Exclusive licenses. Patent license agreements are basically subject to and refer to the provisions of the agreement adopted by the Indonesian State in the Indonesian Civil Code. In this day and age the licenses as outlined in the agreement have the form of standard agreements or standard contracts, in a licensing agreement because it uses a standard contract, it has the potential to cause an imbalance of the parties because some licensing agreements (Lisensor) use clauses that can harm the licensee (License). Refressive legal protection is used, if a license agreement with a standard contract or standard contract used by the licensor of the patent (Licencor) to the recipient of a patent license (License), if it violates a subjective condition in making a patent license agreement then it will cause legal consequences can be canceled (Vernietigbaarheid) whereas if it violates an objective condition it will have legal consequences null and void (Neitigbaarheid).